Edukasi Pencegahan Penyakit Tidak Menular pada Lansia untuk Meningkatkan Kualitas Hidup - Fatma Nuraisyah; Jihan Srikandhia Purnama; Yusni Nuryanti; Rizki Dika Agustin; Ririn Desriani; Mega Utami Putri (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
The healthy living community movement (GERMAS) is a continuous and organized activity carried out jointly by all components of the nation with awareness, desires, and the ability to behave in a healthy manner to improve the quality of life. In improving the quality of healthy life in everyday life, it is necessary to have more extensive knowledge about GERMAS to implement it. Therefore, further education needs to be done one of them by doing physical activity through elderly exercise. The goal in the intervention of community service activities is to improve the health status of the elderly. The method used in this intervention is counseling. The stages are lectures, questions and answers, discussions, and elderly exercises. The intervention target was the elderly in Sorowajan Hamlet who was very enthusiastic and gave positive responses and actively participated in this activity. With this activity, the elderly in Sorowajan Hamlet became more aware of non-communicable diseases (hypertension) and how to prevent them as well as knowing how to maintain quality of life, one of them by physical activity.